(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
The paper reports on teachers and learners viewpoints regarding changing of classrooms during teaching and learning in the primary schools. The study was conducted in the Potgietersrus circuit, Limpopo province South Africa. Changing of classroom process is observed in the intermediate and senior phases purposefully to access resources, for physical space and to receive different learning activities. The changing of classrooms is blamed for causing confusion, disruption during rotation, loss of familiarity in the school to the learners and to the teachers as well. Drawing of Vigotsky ‘s active learning theory that suggest that learning and teaching should be child-centred, we proposed to put attention on how classroom changing should be implemented and who is more suitable to change classrooms .The study employed a qualitative approach with a descriptive case study design. Data was collected through interviews with fifteen participants from three primary schools in the Waterberg district. Data was analysed through thematic analysis. The findings included that the most preferable candidates to change classrooms are the learners. This was based on the argument that teachers use valuable resources to enhance their lesson presentations and learners changing classrooms will keep them active throughout